Parental knowledge, information sources, and perceptions of child road safety in the Klang Valley: implications for road safety initiatives in Malaysia - Mohamad Latip, Nur Fatihah; Sidek, Suriati; Othman, Norainy (Asian Scholars Network, 2023)
Children in Malaysia are vulnerable to road traffic injuries, accounting for 14% of deaths among children those aged five to fourteen. Previous literatures have suggested that parental perceptions of road safety for their children play important role in reducing road traffic accidents and injuries. However, it has been observed that parents may receive inaccurate information from various sources and may have insufficient knowledge regarding child road safety. This lack of knowledge can ultimately impact parental attitudes towards child road safety. Therefore, this study aims to investigate parental knowledge, sources of information and perception of road safety for children in Klang Valley. It was hypothesised that the parental’s knowledge and sources of information predicted parental’s perception on children’s road safety. A total of 215 participants were recruited through purposive sampling with inclusion criteria specifying parents living with children in the Klang Valley, with children aged 5 to 15 years old. The study adopted a cross-sectional survey design, utilizing scales to assess: i) parental sociodemographic background, ii) parental perception on road safety iii) Parental knowledge on road safety and iv) Sources of information on road safety. The results obtained from multiple linear regression indicated that both knowledge and sources of information significantly predicted parental perception F (2, 212) = 29.294, p < .05 with an R2 = .217. In conclusion, these findings have potential to support the efforts of the Malaysian Institute of Road Safety Research (MIROS) and other relevant authorities in Malaysia to develop guidelines for parents and play an active role in providing reliable information related to road safety for children.